Heterogeneity in lots of fiscalized rice seeds cv. BR IRGA 409 - Torres, Salvador Barros; Filho, Orlando Antônio Lucca; Franco, Daniel Fernandez; Siewerdt, Frank (Pesquisa Agropecuaria Brasileira, 1995)
The objective of the present work was to verify the uniformity of rice seeds (Oryza sativa L.) lots cv. BR IRGA 409, by the heterogeneity test. Eight lots of size 1-50, 51-100, 101-150, 151-200, 201-250, 251-300, 301-350 and 351-400 bags were used, and submitted to the sampling intensities of 17, 25, 30, 40, 50, 60, 70 and 80 bags, respectively. The attributes tested were physical purity percentage, number of red and black rice seeds, number of seeds dehulled, germination percentage and number of normal seedlings verified in the cold test. The obtained results showed the following conclusions: independently of the lots sizes and sampling intensities, the values of (H) didn't showed significant heterogeneity for the studied attributes; and the modified cold test was the better attribute for the determination of the heterogeneity of rice seed lots.